PERAN MEDIASI CITRA MEREK DAN KEPERAYAAN MEREK PADA PENGARUH IDENTITAS MEREK TERHADAP LOYALITAS (Studi Kasus pada Motor Yamaha ) - Cecilia Marvelyn; Dergibson Siagian (Jurnal Manajemen, 2020)
The purpose of this study was to determine the role of mediation between brand image and brandtrust on the influence of Brand Identity on Brand Loyalty for Yamaha Motorcycles. The datacollection method in this research is using the communication method. Therefore, the onlinequestionnaire was distributed through Google Docs as many as 142 respondents who owned Yamahamotorbikes. The procedure used for model testing and data processing is the structural equationmodel (Structural Equation Model) using WarpPLS 6.0. The conclusion obtained shows that BrandIdentity has a positive and significant effect on Brand Image, Brand Identity has a positive andsignificant effect both directly and indirectly on Brand Trust, Brand Identity has a positive andsignificant effect on Brand Loyalty, Brand Image has a positive and significant effect on Brand Trust, Brand Image has a positive effect directly and indirectly on Brand Loyalty, Brand Trust has apositive and significant effect on Brand Loyalty. Brand Image is a variable that has the highestmediation effect on the relationship between Brand Identity and Brand Loyalty